Manhaj Ta’līm al-Lugah al-Arabiyyah fi al-Ma’āhid al-Salafiyyah (Dirāsah Taqwīmiyyah min Manẓūr Manhaj Ta’līm al-Lugah al-Arabiyyah li al-Nāṭiqīna bi Gairiha) - Ahmad Ubaedi Fathuddin (Arabic Education Program IAIN Pekalongan, 2021)
This current research departs from concerns over the conventional Arabic teaching in the salaf pesantren (Islamic boarding school) which is not in accordance with the Arabic teaching curriculum for foreign language speakers. It aims to find out the right steps to design the curriculum so that objectives of Arabic learning can be achieved. Using a qualitative approach with a multi-case design, this study took place in three salaf pesantrens in Java, namely Pesantren As-Salafi of Ciwaringin West Java, Pesantren Al-Hikmah 2 of Benda Central Java, and Pesantren HM Al-Mahrusiyah of Lirboyo East Java. Data were collected through in-depth interviews, participatory observation, and documentation review. The study found that although, in general, the Arabic curriculum in the three salaf pesantren was quite suitable with the Arabic teaching curriculum for foreign language speakers, the right steps in designing the curriculum were still needed. First, the four language skills must receive good attention, especially the speaking skills considering the main function of language as a means of communication. Second, the curriculum material must contain three language competencies, i.e. the linguistic aspect, the function of language as a communication tool, and the cultural aspect. Third, the learning system needs to use a combination of several methods by considering the learning objectives, the material characteristics, the students' ability, and even the teachers’ condition. Fourth, modern learning media such as language laboratories need to be pursued because almost all the main objectives of language teaching can be carried out in such laboratories. Fifth, the evaluation of language learning must include mastery of linguistics and communication.